The Influence of Self Efficacy and Organizational Citizenship Behavior on Employee Performance in PT Employees. Pos Indonesia KCU Medan 20000 - Surbakti, Aja Nur’aini; Dirbawanto, Nana Dyki (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to ascertain how self-efficacy and organizational citizenship behavior relate to each other and influence the performance of PT workers. Pos Indonesia KCU Medan 20000. Quantitative methods were used in this research. Those who took part in this research included: PT staff. Pos Indonesia KCU Medan 20000. The sample taken from participants in this research involved 56 participants. Purposive sampling was used in this research as a sample for a strategy. This research information collection method uses Likert scale measurements. This research uses several methods for data analysis such as validity testing, reliability testing, multiple correlation analysis, multiple linear regression analysis, and SPSS-based hypothesis testing. The analysis findings show that organizational citizenship behavior and partial and simultaneous self-efficacy both have a positive impact on employee performance.